Characterization of Strength, Endurance and Lung Function in Subjects with Neuromuscular Diseases with the r577x Polymorphism of the actn3 Gene; [Caracterización de Fuerza, Resistencia y Función Pulmonar en Sujetos Con Enfermedades Neuromusculares Con el Polimorfismo r577x del Gen actn3 - Cifuentes-Silva, E (Sociedad Chilena de Pediatria, 2023)
The ACTN3 R577X polymorphism determines the expression of alpha-actinin 3 protein in human muscle. The homozygous XX genotype fails to synthesize alpha-actinin 3 and is associated with lower muscle strength than the RR genotype. Neuromuscular diseases (NMD) generate an accelerated loss of muscle strength, and their relationship with the ACTN3 gene has not been established. Objective: To describe the variables of strength, respiratory muscle endurance, and lung function in patients with NMD who present the ACTN3 R577X polymorphism. Patients and Method: Descriptive observational study. Six subjects between 10 and 14 years old, with a diagnosis of NMD, treated at the Hospital Dr. Exequiel González Cortés in Santiago, Chile, were evaluated. They were genotyped with the ACTN3 R577X polymorphism by polymerase chain reaction (PCR). Lung function was measured by spirometry. Muscle strength was evaluated with maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP), and grip strength (GS). Respiratory muscle endurance was evaluated by time limit (TLim). Results: The median and 25–75th percentile [Med(p25-p75)] of the lower limit percentages (%Li) for GS, MIP, and MEP were: 36.01% (16.88-53.30), 68.88% (41.07-89.59), and 38.74% (27.74-56.90), respectively. The Med(p25-p75) of TLim was 299.0 (113.3-356.3) seconds. Regarding the genotyping of the ACTN3 R577X polymorphism, in 2 subjects it was XX, in 2 RX, and in 2 RR. Conclusions: The subjects presented restrictive ventilatory spirometric alterations and decreased muscle strength when compared with the reference values. No relationship could be established with the ACTN3 gene polymorphism. © 2023, Sociedad Chilena de Pediatria. All rights reserved.